Context-Based Learning and its Influence on Pupils Reading Accomplishment - Kusmartini, Sri Endah (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
In academic classes and professional settings, some researchers have indicated that context-based learning can affect students' academic success. Unfortunately, it was difficult to find research on the connection between the approach and students' reading achievement. Therefore, the researcher aimed to investigate how context-based learning affects students' reading success. It was a quantitative correlational research that included 63 individuals from the State Polytechnic of Sriwijaya. The data on context-based learning were collected from the viewpoints of the students The data regarding the dependent variable were collected through the score of the tests. The research found a strong and significant link between context-driven learning and achievement in reading (R = 0.679). The R-squared value was 0.462. It means that the contribution of contextual learning to students’ reading success was 46.2%. Additional variables not included in this model impacted the remaining 53.8%. Keywords: Context-based learning, reading accomplishment, reading fluency, reading comprehension